IMPACT OF ANTIOXIDANT SUPPLEMENTATION ON TOXICITY OF METHOTREXATE-AN IN VITRO STUDY ON ERYTHROCYTES USING VITAMIN E - Dhanesha, Manasvee; Singh, Kanchanlata; Bhori, Mustansir; Marar, Thankamani (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â  Objective: Methotrexate (MTX) is an antimetabolite used widely in cancer and autoimmune diseases as an inhibitor of the enzyme dihydrofolate reductase. Treatment regimens with MTX lead to the formation of reactive oxygen species and are involved in drug-induced toxicity presenting severe side effects. In the present investigation, red blood cells were used as a model to understand drug-mediated hemolysis and alterations in antioxidant defense system stimulated by MTX. This effort attempts to evaluate, whether pre-supplementation of vitamin E can modulate drug induced toxicity. Methods: Blood samples from healthy subjects were collected and processed to obtain 10% RBC solution in saline. This solution was further treated with 80Î¼M MTX in presence and absence of 90Î¼M vitamin E respectively. Treated and control RBC solutions were used to assess percent hemolysis, levels of lipid peroxides, GSH, lactate dehydrogenase and activities of specific antioxidant enzymes. Results: Our study reveals a significant increase in lipid peroxides, reduced glutathione GSH reductase activity after incubation with MTX, lactate dehydrogenase, and a considerable decline in catalase, superoxide dismutase, GSH peroxidase, GSH S-transferase, and GSH reductase after incubation with MTX. Conclusion: Ameliorative effect of vitamin E supplementation reduces oxidative stress and restores the activities of these antioxidant enzymes, thereby demonstrating the protection rendered by vitamin E. Our data indicates that vitamin E administration during chemotherapy is effective in modulating the chemotherapy-induced side effects thus stressing on the importance of vitamin E supplementation in combination with chemotherapy during cancer treatments. Keywords: Antioxidant, Lipid peroxides, Superoxide dismutase, Glutathione, Catalase, Red blood cell.